Indonesian medicinal plants as sources of secondary metabolites for pharmaceutical industry - Eti Nurwening Sholikhah (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2016)
Medicinal plants are widely used in traditional medicine in both underdeveloped anddeveloping countries in the word until now. Some secondary metabolites isolated frommedicinal plants have been developed as modern drugs. New antimalarial artemisinin isan example of modern medicine that developed from Artemisia annua L, a plant usedin China since 4,000 years ago. Indonesia is endowed with a rich natural resource.The biodiversity comprises thousands plant species. Therefore, Indonesian flora andfauna are a remarkable opportunity for the development of secondary metabolites forpharmaceutical industry. The Indonesian National Agency for Drug and Food Control,Republic of Indonesia (Badan Pengawas Obat dan Makanan, Republik Indonesia = BPOMRI) classifies traditional medicine into three classes, namely jamu (Indonesian indigenoustraditional medicine), standardized herbal medicine and phytopharmaca based on itsscientific evidences. The BPOM also determined 9 medicinal plants for focusing researchfor drug development. This paper discusses some secondary metabolites and theirpharmacological activities of the following 9 selected Indonesian medicinal plants namelyPiper retrofractum Vahl, Andrographis paniculata Ness, Curcuma xanthorrhiza, Psidiumguajava L, Syzigium polyanthi, Morinda citrifolia, Guazuma ulmifolia Lamk, Zingiberofficinale, and Curcuma domestica collected from various publications. Furthermore,several modern drugs derived from medicinal plants are also discussed.